Melatonin Relations With Respiratory Quotient Weaken on Acute Exposure to High Altitude - Tapia, Marcelo; Wulff-Zottele, Cristian; De Gregorio, Nicole; Lang, Morin; Varela, Héctor; Josefa Serón-Ferré, María; Vivaldi, Ennio A.; Araneda, Oscar F.; Silva-Urra, Juan; Gunga, Hanns-Christian; Behn, Claus (Frontiers in Physiology, 2018)
High altitude (HA) exposure may affect human health and performance by involving the body timing system. Daily variations of melatonin may disrupt by HA exposure, thereby possibly affecting its relations with a metabolic parameter like the respiratory quotient (RQ). . Sea level (SL) volunteers (7 women and 7 men, 21.0 ± 2.04 y) were examined for daily changes in salivary melatonin concentration (SMC). Sampling was successively done at SL (Antofagasta, Chile) and, on acute HA exposure, at nearby Caspana (3,270 m asl). Saliva was collected in special vials (Salimetrics Oral Swab, UK) at sunny noon (SMCD) and in the absence of blue light at midnight (SMCN). The samples were obtained after rinsing the mouth with tap water and were analyzed for SMC by immunoassay (ELISA kit; IBL International, Germany). RQ measurements (n =12) were realized with a portable breath to breath metabolic system (OxiconTM Mobile, Germany), between 8:00 PM and 10:00 PM, once at either location. At SL, SMCD and SMCN values (mean ± SD) were respectively 2.14 ± 1.30 pg/ml and 11.6 ±13.9 pg/ml (p<0.05). Corresponding values at HA were 8.83 ± 12.6 pg/ml and 13.7 ±16.7 pg/ml (n.s.). RQ was 0.78 ± 0.07 and 0.89 ± 0.08, respectively, at SL and HA (p<0.05). Differences between SMCN and SMCD (SMCN - SMCD) strongly correlate with the corresponding RQ values at SL (r = - 0.74) and less tight at HA (r = - 0.37). Similarly, mean daily SMC values (SMC) tightly correlate with RQ at SL (r = - 0.79) and weaker at HA (r = -0.31). SMCN – SMCD, as well as, SMC values at SL, on the other hand, respectively correlate with the corresponding values at HA (r = 0.71 and r = 0.85. Acute exposure to HA appears to loosen relations of SMC with RQ. A personal profile in daily SMC variation, on the other hand, tends to be conserved at HA.-